"Do You Want Me to Become a Social Piranha?": Smarts and Sexism in College Women's Representation in the US TV Show, Greek. Issue 3 (2nd September 2018) - Reynolds, Pauline J.; Mendez, Jesse Perez; Clark-Taylor, Angela
Abstract : This qualitative study utilizes feminist media analysis to examine the depiction of college women in the U.S. TV show Greek . Overall women engage in and graduate from higher education at rates greater than men, but representations of higher education in popular culture tend to minimize women's intellectual engagement within the academy. Our findings focus on two themes emerging from our analysis: that of the show's depiction of college women as "intellectual-lite" through portrayals of their limited and stereotypical interests, and their depictions as "knowers, " portrayed through the ways they make sense of college and how they engage in it. As artifacts of popular culture, such as TV shows, provide templates of college student identity and behaviors for viewers, we close with recommendations to challenge continuing misrepresentations within personal and institutional practice in higher education by suggesting ways to recognize and counter these messages.